Rancang Bangun Aplikasi Penjualan Barang Pada Toko KPRI Toko "Bahagia" Candi Sidoarjo - Krisna, Ockytavia Nila; Nurcahyawati, Vivine; Soebijono, Tony (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2016)
Koperasi Pegawai Republik Indonesia (KPRI) "Bahagia" is a business cooperatives engaged in the sale of goods, savings and loans to members in the sale of goods, the cooperative has a business field stores, in stores KPRI "Bahagia" there are some problems, errors high in the process of recording so that data is not in accordance with these transactions, search history data that most sales of goods sold, sales transaction data storage which has also still in the form of documents and inventory can not see inventory is empty.Of these problems, we need a system that can help in addressing the problems that occur with making the system where the system is design application sale of goods at KPRI â€œBahagiaâ€, Â With a system that has been created it will be able to overcome the problems that occurred in the cooperative.The test is done by inserting a few transactions that have different cases of this type of sale. From the test results, the system can generate sales transaction information required by the cooperative to undertake an evaluation.Keywords: Applications, the Sale of Goods Stores KPRI "Bahagia"